The Efficiency of Garlic Supply Chain Actors Measured using Data Envelopment Analysis (DEA) Method in Karanganyar, Indonesia - Betha Wahyuningtyas; Kusnandar Kusnandar; Sutrisno Hadi Purnomo (Caraka Tani: Journal of Sustainable Agriculture, 2020)
One of the obstacles to the development of agribusiness is related to supply chain management. The availability of supply is the most important factor in influencing supply chain performance. Without a stable and routine supply, supply chain performance will be disrupted. Karanganyar Regency is one of the production centers of horticultural commodities, particularly garlic. This study aimed to analyze the efficiency of each garlic supply chain actor in Karanganyar Regency. The research was conducted from March to April 2019. The efficiency of each supply chain actor in this study was measured using Data Envelopment Analysis (DEA) method. Performance measurement was done through the DEA approach and the performance attributes were input and output variables. The respondents observed were 50 farmers and 13 supply chain actors working in institutions. The samples of farmers were taken using purposive sampling technique, while the samples of supply chain actors were obtained using snowball sampling. The results have shown that the most efficient supply chain actors were retailers with an efficiency value of 1 (100%), while inefficient supply chain actors were farmers with an average efficiency value of 0.709. From a total of 50 Decision Making Unit (DMU) of total farmers, 13 DMU (26%) were efficient, while 37 DMU (74%) were inefficient and further need improvements, like using certified seeds and suitable fertilizer recommendations, as well as reducing external labor during the process of maintenance, harvesting and post-harvest. Farmers are expected to have the desire to learn from referral farmers.